Mimosa hamata Willd. : A Review on Ethnobotanical, Phytochemical and Pharmacological Profile - Parvej, S. (International Journal of Pharmaceutical & Biological Archive, 2017)
Mimosa hamata willd. is a flowering shrub of Mimosacae family which is used in various traditional medicines to cure various diseases. Mimosa hamata willd. and Mimosa pudica are also known as Touch-me-not plant. This weed have been known to posses anti asthmatic, wound-healing, analgesic, anti-inflammatory, contraceptive, anti-microbial, anti-viral, anti-fungal, antioxidant, anti-diarrheal blood-purifier and contraceptive properties in ancient literatures. A wide range of chemical compounds including 4-ethyl-gallic acid, triterpinic saponin A, B, ethylgallate, mimonoside A, B, C, etc have been isolated from this plant. Present review summarizes the information concerning botany, ethnopharmacology, phytochemistry, biological activity of Mimosa hamata willd.